2020
DOI: 10.3934/jimo.2018142
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cuckoo Search algorithm for numerical function optimization

Abstract: Cuckoo Search (CS) is a recently proposed metaheuristic algorithm to solve optimization problems. For improving its performance both on the efficiency of searching and the speed of convergence, we proposed an improved Cuckoo Search algorithm based on the teaching-learning strategy (TLCS). For a better balance between intensification and diversification, both a dynamic weight factor and an out-of-bound project strategies are also introduced into TLCS. The results of numerical experiment demonstrate that our imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…where pa (r) ∈[0.15,0.55]; pa (r)min represents the minimum values of pa (r) ; pa (r)max represents the maximum values of pa (r) ; rand () is a random number generated uniformly distributed between (0,1); τ (a, b) is a gamma-distributed random number obeying shape parameter a and scale parameter b; and λ is used to control the deviation between the inertia weight and the expected value [37]. ( 23)…”
Section: Algorithm Flowmentioning
confidence: 99%
“…where pa (r) ∈[0.15,0.55]; pa (r)min represents the minimum values of pa (r) ; pa (r)max represents the maximum values of pa (r) ; rand () is a random number generated uniformly distributed between (0,1); τ (a, b) is a gamma-distributed random number obeying shape parameter a and scale parameter b; and λ is used to control the deviation between the inertia weight and the expected value [37]. ( 23)…”
Section: Algorithm Flowmentioning
confidence: 99%
“…A cuckoo spawns in another birds' nest [18]. If the nest owner finds these exotic birds' eggs, they will abandon their young or look for a new nest [19].…”
Section: The Standard Cuckoo Search Algorithm (Cs)mentioning
confidence: 99%
“…Entomologists have found that gulfs raise their young ones by depositing in other birds' nests rather than building their nests [28]. However, these exotic birds' eggs may be discovered by the host, which may abandon the young birds or rebuild the new nest [29].…”
Section: The Standard Cs Algorithmmentioning
confidence: 99%
“…The standard CS algorithm uses levy flight random walk and preference random walk strategies to update the nest locations. However, due to the uncertainty of the random walk, the search capability gets weaker, and the convergence speed also slows down [28]. In ISCS, a nonlinear decreasing inertia weight and the adaptive scaling factor are proposed to enhance convergence speed and solution accuracy.…”
Section: The Iscs Algorithmmentioning
confidence: 99%